CapABLEinvest / Muhammad Hakim Abdul Wahid … [et al.] - Abdul Wahid, Muhammad Hakim; Mohamad Zubir, Putera Haiqal; Mohamad Shaharin, Muhammad Alif; Rosli, Aishah; Mohd Fuad, Farhanah Adilah; Azizan, Nur Aqilah; Wan Ismail, Wan Musyirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
At this point, the country's level of achievement in guaranteeing access to digital application facilities for disabled people is still far compared to the standard in developed countries. Furthermore, people with disabilities are given less attention to the importance of investment and stock trading. Therefore, to make it easier for people with disabilities to invest and trade stocks, we designed an exceptional application known as CapABLEinvest that navigates for people with disabilities (OKU). The application provides services, including online appointments and consultations with stockbrokers, stock trading, and investment services. The specialty provided is that the application offers text-based conversations and video calls with sign language interpretation that increases accessibility for individuals with disabilities. By just using the phone's camera, disabled users who are deaf or mute can communicate and receive information quickly through the help of an interpreter who helps them talk. Furthermore, the app provides customization options by allowing users to customize the app interface according to their preferences, including choosing a preferred language, font style, and communication settings. This application also utilized a voice command technology system for users with mobility impairment or blindness. By incorporating these features, this app service for people with disabilities can help bridge communication barriers and increase access to investment and trade facilities for people with disabilities. Therefore, we ensure that this website is suitable for people with disabilities to access so that this group does not continue to be marginalized and ensure that they can also be involved in the digital economy.